Validating The Use of Comic Strips as Instructional Materials to Address Environmental Issues - Alvarez, Jhondel S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The aimed of this study was to investigate the possibility of using comic strips as teaching materials to address environmental issues related to the over-exploitation of deep wells, which was one of the main environmental problems in Tabango, Leyte. In essence, the goal of this study is to address this issue because people often lack awareness of the implications of their actions. The efficacy of rubric ratings was employed by the investigator to assess the calibre of the comic strips generated. The researcher created a comic strip as instructional material using a descriptive-developmental design, and validators would act as the study's primary respondents. Their opinions about how the comic strips were used were obtained as primary data regarding the application of these educational resources. The research concluded that the validated comic strip was reliable, and the developed comic strips were found to be useful, appropriate, and effective in addressing the issue of overuse of deep wells due to the reason that most of the expert validators have a weighted average of 0.98, 0.54, 1.08, 1.16, 1.18 having an overall interpretation as “AGREE”. Thus, the study highlights the potential of utilizing comic strips as educational material for environmental issues.